2021
DOI: 10.15403/jgld-3308
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelationship Among Non-Alcoholic Fatty Liver Disease, Colonic Diverticulosis and Metabolic Syndrome

Abstract: Non-alcoholic fatty liver disease and colonic diverticulosis are widespread, obesity-related diseases. It hasrecently become clear that non-alcoholic fatty liver disease is a systemic disease and may play a key rolein metabolic syndrome; therefore, the term metabolic-dysfunction-associated fatty liver disease has beenintroduced in the literature. Excess visceral adipose tissue is an important predictor of complications in bothnon-alcoholic fatty liver disease and colonic diverticulosis. Current evidence sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…It has been established that NAFLD is strongly associated with other metabolic comorbidities, including obesity, type 2 diabetes, dyslipidemia, cardiovascular disease, colonic diverticulosis, and neurodegenerative conditions [ 1 , 4 , 5 , 6 , 7 , 14 , 91 ]. Hepatic steatosis, which refers to a pathological state of the liver characterized by an accumulation of lipid content at over ~5% of the total organ weight, is closely associated with insulin resistance in multiple organs, as supported by several studies demonstrating impaired insulin action in both lean and non-diabetic obese individuals [ 14 , 92 , 93 , 94 ].…”
Section: Hepatokines and Nafldmentioning
confidence: 99%
“…It has been established that NAFLD is strongly associated with other metabolic comorbidities, including obesity, type 2 diabetes, dyslipidemia, cardiovascular disease, colonic diverticulosis, and neurodegenerative conditions [ 1 , 4 , 5 , 6 , 7 , 14 , 91 ]. Hepatic steatosis, which refers to a pathological state of the liver characterized by an accumulation of lipid content at over ~5% of the total organ weight, is closely associated with insulin resistance in multiple organs, as supported by several studies demonstrating impaired insulin action in both lean and non-diabetic obese individuals [ 14 , 92 , 93 , 94 ].…”
Section: Hepatokines and Nafldmentioning
confidence: 99%
“…Recent studies that have looked at obesity and associated diseases have shown a direct relationship between visceral fat, non-alcoholic fatty liver disease, and diverticulosis. The relationship between the intestinal microbiome and the metabolic syndrome has been followed since 2013 [ 13 ], but dysbiosis and non-alcoholic fatty liver disease and diverticulosis appear in the most recent studies [ 14 ]. It seems that the disease of the fatty liver, visceral fat, and diverticulosis is the consequence of a marked dysbiosis, present in the metabolic syndrome [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has recently suggested that NAFLD is a systemic disease which plays a critical role in metabolic syndrome; accordingly, the concept metabolic-dysfunction-associated fatty liver disease (MAFLD) has been proposed [ 5 ]. Excessive visceral adiposity in MAFLD, leading to a pro-inflammatory state, is an important risk factor for obesity-related complications such as colonic diverticulosis, which has the bi-directional relationship between metabolic syndrome or NAFLD [ 6 ]. NAFLD is a common liver disease characterized by fat accumulation in the liver in those individuals who do not drink heavily (>210 g in males and >150 g in females per week) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%